Pengaruh kompetensi pedagogik, motivasi kerja dan supervisi akademis terhadap kinerja guru madrasah aliyah se Kota Yogyakarta - Hartiningsih Hartiningsih; Sumadi Sumadi (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aimed to determine: (1) the influence of teachers’ competence,  motivation, and academic supervisor simultaneously on the performance of MAN in Yogyarta. (2) The influence of teachers’ competence on the performance of MAN in Yogyakarta. (3) The influence of the motivation on the teachers’ performance of MAN in Yogyakarta (4) The influence of motivation on teachers’ performance of MAN in Yogyakarta. The research method used was a survey with a sample of all MAN teachers in Yogyakarta. The data was collected by using questionnaires that had been tested on 30 respondents and had fulfilled the validity qualification with Pearson correlation techniques and reliability requirements with Cronbach alpha. The data analysis technique was using descriptive analysis and multiple linear regression analysis, which had been previously tested for normality, multicollinearity, and linearity test. The results of the research show that (1) Teachers’ competence, work motivation, and academic supervisor simultaneously have a positive influence on the performance of MAN in Yogyakarta, (2) Teachers’ competence has a positive influence on the performance of MAN teachers in Yogyakarta. (3) The motivation has a positive influence on the performance of MAN teachers in Yogyakarta. (4) Motivation has a positive influence on the performance of MAN teachers in Yogyakarta. It means that the higher and the better of the teachers’ competence,  motivation, and academic supervisor will lead to the better teachers’ performance. On the contrary, the lower and the worse of the teachers’ competence, motivation, and academic supervisor will lead to the lower teachers’ performance. Meanwhile, teachers’ competence has the most significant influence among them. Therefore, the  MAN teachers in Yogyakarta are strongly expected to develop their competence to have a better performance.